ULTRA PETITA CONSTITUTIONALITY IN THE CONSTITUTIONAL COURT - Mohamad Safrin; Maulana Amin Tahir (Qaumiyyah: Jurnal Hukum Tata Negara, 2025)
In making a decision on a judicial review case, ideally the Constitutional Court decides according to what the applicant requested in his/her application, but in practice the Constitutional Court often decides a case beyond what the applicant requested, or in other words, is ultra petita. This is actually contrary to the provisions in Article 45A of Law Number 8 of 2011 concerning Amendments to Law Number 24 of 2003 concerning the Constitutional Court, which prohibits the Constitutional Court from deciding ultra petita. The study used a normative legal method that focused on the legal aspect with a literature study approach. The results of the study show that the legislators wanted the Constitutional Court not to decide more than what the applicant requested because of the nature of the Constitutional Court's decision, which is final and binding. However, in subsequent cases, the provisions regarding the prohibition of ultra petita were also found to be contradictory by the Constitutional Court itself, namely through the Constitutional Court's decision Number 48/PUU-IX/2011 concerning the judicial review of Law Number 35 of 2009 concerning Narcotics and Law Number 8 of 2011 concerning Amendments to Law Number 24 of 2003 concerning the Constitutional Court, shortly after the enactment of Law Number 8 of 2011. The Constitutional Court, in deciding constitutional cases, must avoid actions that exceed its authority while still prioritizing the values ​​of truth and justice that apply in society. However, the application of ultra petita is not without limitations, because it raises challenges that can weaken the effectiveness of the judiciary and has the potential to invite arbitrariness in judicial decision-making. Abstrak Dalam memberikan putusan terhadap suatu perkara pengujian undang-undang, idealnya Mahkamah Konstitusi memutus sesuai dengan apa yang dimohonkan pemohon dalam permohonannya, namun dalam praktiknya Mahkamah Konstitusi sering kali memutus suatu perkara melebihi apa yang dimohonkan pemohon atau dengan kata lain bersifat ultra petita. Hal tersebut justru bertentangan dengan ketentuan dalam pasal 45A Undang-Undang Nomor 8 Tahun 2011 tentang Perubahan Atas Undang-Undang Nomor 24 Tahun 2003 tentang Mahkamah Konstitusi yang melarang Mahkamah Konstitusi untuk memutus secara ultra petita. Penelitian menggunakan metode yuridis normatif yang difokuskan pada aspek yuridis dengan pendekatan studi kepustakaan. Hasil penelitian menunjukkan bahwa pembentuk undang-undang menghendaki agar Mahkamah Konstitusi tidak memutus lebih dari apa yang dimohonkan pemohon dikarenakan sifat putusan Mahkamah Konstitusi yang bersifat final dan mengikat. Akan tetapi, pada perkara-perkara selanjutnya, ketentuan mengenai larangan ultra petita tersebut juga ditemukan kontradiksi oleh Mahkamah Konstitusi sendiri, yaitu melalui putusan Mahkamah Konstitusi Nomor 48/PUU-IX/2011 tentang pengujian Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika dan Undang-Undang Nomor 8 Tahun 2011 tentang Perubahan Atas Undang-Undang Nomor 24 Tahun 2003 tentang Mahkamah Konstitusi, sesaat setelah diundangkannya Undang-Undang Nomor 8 Tahun 2011. Mahkamah Konstitusi dalam memutus perkara konstitusi harus menjauhi tindakan yang melampaui kewenangannya dengan tetap mengutamakan nilai-nilai kebenaran dan keadilan yang berlaku dalam masyarakat. Meskipun demikian, penerapan ultra petita bukannya tanpa keterbatasan, karena menimbulkan tantangan yang dapat melemahkan efektivitas peradilan dan berpotensi mengundang kesewenang-wenangan dalam pengambilan keputusan peradilan.